Torsion of a circular anisotropic beam with two linear cracks weakened with a circular cavity - Eyvazov, Etimad Bayramoğlu; Oge, Mecit (Polish Society of Theoretical and Allied Mechanics Al. Armii Ludowej 16 p. 650 Warszawa 00637, 2017)
Various components made of anisotropic materials (plast-mass, glass material, etc.) have been widely used in the production of modern mechanisms and machinery. Precise calculation of these elements, constituting the design, holds great importance. In general, fracture and distribution are essential issues in safety calculations. In this study, torsion of a beam with an S oblast having outer and inner constraints as L2 and L1 circles with R2 and R1 radii, respectively, is investigated. © 2020 Elsevier B.V., All rights reserved.
Keywords: Affine Connections; Anisotropic Medium; Conformal Mapping Functions; Isotropic Beams; Orthotropic Beams